Review on Ethanomedicinal and Pharmacological Properties of Ficus religiosa - Amandeep Kaur, A. C. Rana, Vineeta Tiwari, Ramica Sharma, Sunil Kumar (Journal of Applied Pharmaceutical Science)
Ficus religiosa (Bo tree) is the most popular member of the genus Ficus, commonly named as Peepal. Various parts of the plant, like bark, fruit, leaves and seeds are widely used in indigenous system of medicine. F. religiosa showed a wide spectrum of pharmacological activities like, anticonvulsant, anthelmintic, anti-amnesic, anti-anxiety, anti-asthmatic, antibacterial, antioxidant, anti-inflammatory and antiulcer. The present review is an attempt to provide a detailed survey of the literature on traditional uses and pharmacological properties of the plant.
Keywords: Ficus religiosa, anticonvulsant, anthelmintic, anti-amnesic, anti-inflammatory, antiulcer.